Sustainability of Adoption of New Improved Rice Variety Innovation in West Kalimantan Coastal Areas: Review of Social and Cultural Aspects - Bancin, Hardi Dominikus; Ekawati, Ekawati; Rizieq, Rahmatullah; Ellyta, Ellyta (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2024)
As a staple food in Indonesia, rice has significant socio-economic value, especially in regions such as West Kalimantan. However, the variability of rice production poses a challenge to food security and economic stability. This study assesses the sustainability of the adoption of new improved rice varieties (VUBs) in West Kalimantan, focusing on social and cultural aspects using Multi-Aspect Sustainability Analysis (MSA). Focus group discussions and expert interviews were used to identify important factors affecting VUB adoption. The results indicated a sustainable adoption status (54.17%), with potential for improvement (58.33%) in the future. Farmer education emerged as the most sensitive factor, highlighting the need for educational interventions to improve technology access and adoption. In addition, farmers' knowledge of VUB, culture of mutual cooperation, the absence of social conflict, and positive consumer preference for VUB rice are also critical for adoption. Recommendations include targeted educational interventions, improved knowledge dissemination strategies, consideration of the cultural context, conflict management approaches, and market-oriented strategies to sustainably increase VUB adoption. Addressing these factors can contribute to sustainable agriculture and rural development in West Kalimantan and similar contexts, ensuring long-term benefits for farmers and food security.